Klasifikasi Penyakit Stroke Menggunakan Algoritma Decision Tree C.45 - Randi Estian Pambudi; Sriyanto Sriyanto; Firmansyah Firmansyah (TEKNIKA, 2022)
Stroke is a disorder of brain function, both local and comprehensive, which will cause the blood supply to the brain to be disrupted quickly and last more than 24 hours or end in death. Stroke is also one of the deadliest types of disease in Indonesia. The importance of knowing the symptoms of stroke early is an early prevention. Therefore, a study was conducted to analyze data related to the causes of stroke. The attributes involved in the cause of stroke are age, gender, glucose level, history of heart disease, hypertension, type of work, type of residence, smoking status, body mass index and marital status. A certain algorithm is needed to classify all these attributes. Decision Tree C4.5 is the most widely used algorithm, in this case the accuracy of the Decision Tree C4.5 algorithm is 99.07%.